2021
DOI: 10.3390/cells10010119
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Antibodies, Vitamin D and Short-Chain Fatty Acids: Their Correlation with Cell Subsets in Multiple Sclerosis Patients and Healthy Controls

Abstract: Although the etiology of multiple sclerosis (MS) is still unknown, it is commonly accepted that environmental factors could contribute to the disease. The objective of this study was to analyze the humoral response to Epstein-Barr virus, human herpesvirus 6A/B and cytomegalovirus, and the levels of 25-hydroxyvitamin D (25(OH)D) and the three main short-chain fatty acids (SCFA), propionate (PA), butyrate (BA) and acetate (AA), in MS patients and healthy controls (HC) to understand how they could contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
(63 reference statements)
0
7
1
Order By: Relevance
“…In our study, the concentration of acetate, propionate and butyrate were higher compared with previous studies ( 14 , 19 , 42 ). This might be explained by the use of different extraction methods for the detection of SCFAs between the studies.…”
Section: Discussioncontrasting
confidence: 80%
“…In our study, the concentration of acetate, propionate and butyrate were higher compared with previous studies ( 14 , 19 , 42 ). This might be explained by the use of different extraction methods for the detection of SCFAs between the studies.…”
Section: Discussioncontrasting
confidence: 80%
“…By carrying stretches of telomeric repeats at their linear genome, the variants HHV-6A and HHV-6B are able to integrate into human chromosomes and become latent [ 160 ]. This virus has been found in several human diseases, including autoimmunity [ 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 ], ME/CFS [ 190 , 191 , 192 , 193 ], mitochondrial dysfunction [ 193 , 194 ], and in patients with moderate to critical COVID-19 [ 42 , 43 , 44 , 195 , 196 ]. Among the autoimmune diseases associated with HHV-6, the most frequently cited is multiple sclerosis (MS) [ 170 , 171 , 172 , 173 , 174 , 175 , 176 , …”
Section: Multiple Tissue Damage and Autoimmunitymentioning
confidence: 99%
“…This has been demonstrated by the direct detection of the HHV-6 genome and antigens in the blood and brain of patients with MS [ 176 , 177 , 178 , 181 , 182 , 183 ]. Furthermore, not only were higher levels of anti-HHV-6 A/B antibodies detected in the blood of MS patients, their titers also correlated with the severity of the disease [ 170 ] and in predicting risk of relapse [ 184 , 185 , 186 ]. Researchers further concluded that in addition to its potential etiologic role in MS, infection with HHV-6 or immune reaction against it may also have an effect on MS relapse and its progression [ 184 ].…”
Section: Multiple Tissue Damage and Autoimmunitymentioning
confidence: 99%
“…Virtually all (99.5%) patients with MS are seropositive for antibodies directed against EBV ( 22 ). A recent study analyzed multiple environmental factors that may contribute to MS risk, including VitD levels and EBV antibody titers ( 23 ). EBV antibody titers were significantly higher in MS patients and there was an inverse relationship between VitD levels and EDSS, yet no correlation between VitD levels and EBV antibody titers.…”
Section: Multiple Sclerosismentioning
confidence: 99%